Flexible work organization and employer provided training: Evidence from German linked employer-employee data - Annika Campaner; John S. Heywood; Uwe Jirjahn (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2018)
We examine the hypothesis that flexible work organization involves greater skill requirements and, hence, an increased likelihood of receiving employer provided training. Using unique linked employer-employee data from Germany, we confirm that employees are more likely to receive training when their jobs are characterized by greater decision-making autonomy and task variety, two essential elements of flexibility. Critically, the training associated with workplace flexibility does not simply reflect technology. Skill-biased organizational change plays its own role. Moreover, we show that the training associated with workplace flexibility is disproportionately oriented toward employees with a greater formal education. Our results also provide modest evidence of an age bias of workplace flexibility. However, the link between workplace flexibility and training does not appear to differ by gender.
Keywords: J24; L00; M53; 330; Delegation; Multitasking; Skill-Biased Organizational Change; Training